Fc‐fragment removal allows the EPO‐Fc fusion protein to be detected in blood samples by IEF‐PAGE. Issue 11 (December 2015) - Postnikov, Pavel; Krotov, Grigory; Mesonzhnik, Natalia; Efimova, Yulia; Rodchenkov, Grigory
Abstract : EPO‐Fc proteins have been under investigation as a potential drug for treating anaemia and have shown larger half‐life values than other erythropoiesis‐stimulating agents (ESAs). Sodium dodecyl sulfate/sodium N ‐lauroylsarcosinate polyacrylamide gel electrophoresis (SDS/SAR‐PAGE) methods and subsequent immunoblotting are used for routine anti‐doping analysis. This paper reports that EPO‐Fc fusion proteins can be detected in serum samples by isoelectric focusing‐polyacrylamide gel electrophoresis (IEF‐PAGE) in carrier ampholyte‐based gels with a pH 2–6 gradient after removing the Fc part via site‐specific IdeS protease cleavage. The IdeS‐digested EPO‐Fc protein yields three fragments: two Fc fragments and one dimeric EPO‐hinge fragment. After IEF‐PAGE was followed by double Western blotting with chemiluminescent detection, the dimeric EPO‐hinge fragment showed a unique isoelectric pattern, which differed from those of any other currently known analogue of EPO. We observed that the removal of the Fc fragment from EPO‐Fc reduced the apparent molecular weight of entire fusion protein and increased its electrophoretic mobility. As a result, the band for the EPO‐hinge fragment was located in a region between the rEPO and NESP standards, at which lower amounts of serum proteins are present. Simple and selective protocols for determining the EPO‐Fc protein in human serum were developed to extend the methodological anti‐doping arsenal. This protocol has been characterized. The limit of detection (LOD) of the IEF‐PAGE method was 20 pg, and that of SDS/SAR‐PAGE was 15 pg. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : EPO‐Fc fusion proteins can be detected in serum samples by IEF‐PAGE (pH 2‐6) after removing the Fc part via site‐specific IdeS protease cleavage. The dimeric EPO‐hinge fragment showed a unique isoelectric pattern, which differs from those of any other analogue of EPO. The offset of the EPO‐hinge band in the area between the rEPO and NESP standards using SAR/SDS‐PAGE can distinguish EPO‐Fc from the other proteins and may be additional proof of the abuse of this species by athletes.